Conceptualizing Qur’anic Learning Engagement: Integrating Value Co-Creation and Relational Sustainability in the Digital Era - Nur Asiyah; Muhammad Hilmi Labibunnajah; Alamul Huda Almuzakky; Adam Ahmad Alif (J-PAI: Jurnal Pendidikan Agama Islam, 2026)
This study develops a conceptual framework that integrates value co-creation and relational sustainability to explain and support the continuity of Qur’anic reading intensity among children in the digital era. The rapid advancement of digital technology has expanded access to Qur’anic learning through various interactive platforms; however, increased accessibility does not automatically guarantee the quality or istiqamah of children’s reading practices, as digital environments frequently introduce distractions and fragment sustained attention. Using a qualitative approach with a library research design, this study systematically analyzed recent literature from Scopus, Google Scholar, and Garuda databases through thematic content analysis and conceptual mapping. The findings propose that Qur’anic learning should be understood as a relational value ecosystem in which teachers, parents, institutions, and children collaboratively integrate cognitive, affective, and normative-spiritual resources through ongoing interaction. Value co-creation functions as the generative core of this ecosystem, while relational sustainability, encompassing trust (amanah), communicative transparency, and digital engagement, serves as the central mediating mechanism linking collaborative value construction to the stability of children’s reading engagement. Sustainability of engagement emerges as the bridging construct through which relational processes are internalized as self-regulated spiritual practice, ultimately manifesting as stable Qur’anic reading intensity. This study contributes an interdisciplinary framework that repositions Qur’anic education from a purely pedagogical activity to a collaboratively sustained spiritual practice, offering practical implications for institutions, teachers, parents, and educational technology developers committed to nurturing children’s istiqamah in Qur’anic recitation.